Karakterisasi Asap Cair Hasil Pirolisis Sampah Kantong Plastik sebagai Bahan Bakar Bensin - I Dewe Ketut Anom; John Z Lombok (Jurnal Kimia Fullerene, 2020)
Plastic bag waste is garbage that is difficult to degrade in nature. Hoarding plastic bag waste can reduce soil fertility because it cannot be broken down by microorganisms quickly. Burning plastic bag waste can produce toxic gases and have a negative impact on human health and the environment. To solve the problem, the plastic bag waste is converted into liquid smoke as fuel oil. The method used to convert the plastic bag waste into liquid smoke is pyrolysis. The fractionation of liquid smoke at temperatures below 200oC produces 36.20% clear liquid which has similar properties to gasoline fuel. Characterization of the physical and chemical properties of the gasoline fraction liquid smoke has a density of 0.76 g/mL; a viscosity of 0.80 cP; boiling point at 146.9oC; flash point at 30.60oC; a calorific value of 10,520 cal/g; with the octane number of 98 RON. GC-MS analysis shows that the gasoline fraction liquid smoke consists of 45 chemical compounds which can be classified into alkanes, alkenes, cycloalkanes and alcohols.